DETERMINASI PELATIHAN, KOMPETENSI, DAN KOMPENSASI TERHADAP KINERJA PEGAWAI KANTOR PEMUDA DAN OLAHRAGA KOTA BATAM - Indrayani, Indrayani (Universitas Batam, 2019)
This study aimed to analyzed the determination of training, competention, and compensation on employee job performance. This study uses three independent variables, training, competention and compensation with one dependent variable namely performance. The use of variables in this study is expected to determine how the process is going on and what are the factors driving the creation of a good performance in the office of . Samples were 52 people. Samples were taken by sampling techniques. Data analysis method used is quantitative analysis, the validity, reliability test, classic assumption test, multicoloniarity test, heteroscedasticity test, normality test, multiple linear regression analysis, t-test, f- test the coefficient of determination R2.